Schwarze Katze – podwójna biografia Karin Wolff w świetle badań nad tłumaczką - Karolina Kamińska (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2022)
The aim of the above article is to reconstruct the biography of Karin Wolff, a distinguished translator of Polish literature in Germany (more than 90 translations), who was active in the opposition in the GDR and the Polish People’s Republic. The author presents Wolff’s activities to popularize Polish culture (including the organization of a Polish literate salon in Frankfurt/ Oder), her contacts with Polish poets (e.g. Jan Twardowski, Jerzy Ficowski) and her numerous publishing initiatives.